Morphological characteristic and Phenetic Relationship of Lysurus periphragmoides Collected from West Java - Rudy Hermawan; Laifa Fusvita; Naufal Hafizh Nugraha; Mega Putri Amelya (UIN Sunan Gunung Djati Bandung, 2021)
Lysurus is one of the unique genera in Basidiomycetes. It has a stinky odor and slime on the head. The unusual-shaped makes the species in Lysurus easily to be identified. One of Lysurus had been found in West Java, Indonesia namely L. periphragmoides. The specimen was deposited into Herbarium Bogoriense with code BO 24418. This study aimed to obtain specimens and characterize the Lysurus BO 24418 using morphological characteristics, and analyze the phenetic relationship among Lysurus species. Lysurus BO 24418 has two phases (egg and mushroom). The egg phase is usually hypogeous underground. The mushroom has a head and stem. The head bears the mature spore with slime distribute malodor. The stem has a hollow and spongy texture with a yellowish color. The numerical data of morphological characters of species in Lysurus were analyzed using NTSys ver 2.1 software. Ten characters were used to build a dendrogram using Sequential Agglomerative Hierarchical Nested (SAHN) cluster analysis with Unweighted Pair Group Method with Arithmetic Mean (UPGMA). Phallus indusiatus was selected as an outgroup. The analyses showed the specimen was classified as L. periphragmoides with 100% of similarity coefficient and it was close L. gardneri with 40,4% of similarity coefficient. The characters that cluster among them are stem surface, head type, egg diameter, and spore max length